ISOLATION AND SELECTION OF ENDOPHYTE FUNGI FROM THE ANDALIMAN PLANT (Zanthoxylum acanthopodium DC) AS ANTIFUNGAL - Idramsa, Idramsa; Ayu, Nur (Universitas Medan Area, 2025)
Dermatophytosis (Ringworm) is a disease caused by dermatophyte fungal infection that attacks the epidermis (keratin) tissue such as skin, nails and hair in humans. Antibiotics as a drug for fungal infections that are often used by the public are known to have side effects, so that alternative drugs are needed that are relatively safe to use. Endophytic microbes found in plants are known to be an alternative natural medicine that does not have side effects, because they contain bioactive compounds. This study aims to isolate, select and identify endophytic fungi in andaliman plants (Zanthoxylum acanthopodium DC) and determine their potential as antifungals against dermatophytosis fungi. Exploration methods were used, molecular analysis using marker genes Internal Transcribed Spacer (ITS) and antifungal activity tests (Dual culture) against Tricophyton rubrum and Tricophyton mentagrophytes as pathogenic test fungi. The results showed that endophytic fungus from the species Diaporthe phaseolorum (Isolate EF128). has very strong antifungal activity against the test fungus Tricophyton rubrum and is strong against Tricophyton mentagrophytes (isolate IJE D3). so it has the potential as an antifungal.